Efication of Some Entomopatogen Fungus on Green Ladybug Imago (Nezara Viridula Linnaeus) (Hemiptera: Pentatomidae) - Muhammad Agung Permadi; Rafiqah Amanda Lubis; Mukhlis Mukhlis; Imam Aryo Pahlawan; Sulaiman Abdi (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
Green ladybug (Nezara viridula L.) is an important pest in some plants, including soybeans. N. viridula attacks cause a decrease in yield of up to 80%. Environmental friendly pest control studies are needed to overcome the problem of resurgence caused by N. viridula, among others by utilizing entomopathogenic fungus as their natural enemies. This study discusses about the efficacy of entomopathogenic fungi against N. viridula imago. The research is conducted at the Agricultural Agrotechnology Laboratory, Muhammadiyah University of South Tapanuli. The study uses a completely randomized design, nine treatments (control and eight isolates of entomopathogenic fungus) with three replications. The conidia density used is 108 conidia / ml. The entomopathogenic fungus application was performed on N. viridula imago. The results shows that MetKP fungus isolates are able to kill N. viridula imago with the highest mortality rate of 78.33%. The isolates of MetKM fungi and M. anisopliae caused the lowest imago mortality of 61.67%. Isolate of B. bassiana fungus had the lowest LT50 with a time of 5.66 HSA and the isolate of the MetTmM fungus had the highest LT50 with a time of 7.27 HSA. In the immature body part of N. viridula infected with fungus is enveloped by entomopathogenic fungal mycelium.